An Improved Bulged Belly Shrimp Trawl for Inshore Waters - Syed Abbas, M.; Mhalathkar, H.N. (Fishery Technology, 2025)
The effect of Tapering Jibs on a tested design of 15 m bulged belly trawl was studied. The net fitted with tapering jibs consistently landed better shrimp catches and recorded less resistance under tow compared to the control net.